2016
DOI: 10.1002/ajpa.23051
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and functional implications of sexual dimorphism in the human skeletal thorax

Abstract: Number of tables: 2Abbreviated title: 3D morphometrics of human rib cage.Key words: rib cage; geometric morphometrics; sex differences. This is the peer reviewed version of the following article: American Journal of Physical Anthropology 161(3): 467-477 (2016), which has been published in final form at http://dx.doi.org/10.1002/ajpa.23051. This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Self-Archiving. *Corresponding author:2 Title: Morphological and funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
58
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 62 publications
8
58
0
1
Order By: Relevance
“…4) supports an assignment of SD-1619 to a young (and not so large) adult and of SD-1641 to In a more general morphological framework, the current study addressed the hypothesis that the enlarged thorax of Neandertals is not only the result of larger ribs (Franciscus and Churchill, 2002;Gómez-Olivencia et al, 2009;García-Martínez et al, 2014a, Bastir et al, 2015a, but also of a more dorsal orientation of the transverse processes of the thoracic vertebrae (Bastir et al, 2015b). A similar kind of influence of vertebral shape on rib cage morphology has been proposed in Australopithecus (Ward et al, 2012) and Homo ergaster/erectus (Jellema et al, 1993;Latimer and Ward, 1993), and more recently also identified as a geometric feature of modern human sexual dimorphism García-Martínez et al, 2016a). Shape data of both El Sidrón (SD-1641-T3, -T4; SD-1619-T6, -T7) vertebral reconstructions available for 3D analysis (Figs.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…4) supports an assignment of SD-1619 to a young (and not so large) adult and of SD-1641 to In a more general morphological framework, the current study addressed the hypothesis that the enlarged thorax of Neandertals is not only the result of larger ribs (Franciscus and Churchill, 2002;Gómez-Olivencia et al, 2009;García-Martínez et al, 2014a, Bastir et al, 2015a, but also of a more dorsal orientation of the transverse processes of the thoracic vertebrae (Bastir et al, 2015b). A similar kind of influence of vertebral shape on rib cage morphology has been proposed in Australopithecus (Ward et al, 2012) and Homo ergaster/erectus (Jellema et al, 1993;Latimer and Ward, 1993), and more recently also identified as a geometric feature of modern human sexual dimorphism García-Martínez et al, 2016a). Shape data of both El Sidrón (SD-1641-T3, -T4; SD-1619-T6, -T7) vertebral reconstructions available for 3D analysis (Figs.…”
Section: Discussionsupporting
confidence: 64%
“…However, transverse process orientation could also be important for respiratory function. In Homo sapiens, the thoracic capacity of males is greater than in females, both absolutely and relative to stature (Silbernagl and Despopoulos, 1991;Bellemare et al, 2003Bellemare et al, , 2006García-Martínez et al, 2016a). It has been shown recently that the larger male thoracic capacity can be related to a greater dorsal orientation of the transverse processes of their thoracic vertebrae, particularly the lower ones (T6-T9; Bastir et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in contrast to the kidney, pulmonary Gilz mRNA expression, for instance, is upregulated to a greater degree in females compared to males. Recent studies have underlined sex differences in respiratory function during lung development and in adulthood [3,53,54,55]. Moreover, female smokers have an increased risk of chronic obstructive pulmonary disease in comparison to male smokers with similar history of cigarette smoke exposure, both in human and mice; however, the underlying mechanisms are still under investigation [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…They have also recently been shown in various biological processes such as white matter development and brain volume [1], stress response and depression [2] or respiratory function [3]. …”
Section: Introductionmentioning
confidence: 99%
“…Expansion of the lungs during breathing and consequent oxygen intake is facilitated by the action of the intercostal muscles, the diaphragm and other accessory muscles (Spalteholz, 1970;De Troyer et al, 2005). Therefore, oxygen availability, basal metabolic rate (BMR) and physical activity are also dependent on various aspects of rib cage morphology (Franciscus and Churchill, 2002;Churchill, 2006;Froehle and Churchill, 2009;Gómez-Olivencia et al, 2009;García-Martínez et al, 2014, 2016aBastir et al, 2017a). In addition, the rib cage contributes to the configuration of gross trunk shape in hominins due to its morphological integration caudally with the pelvis (Jellema et al, 1993;Bastir et al, 2014a) and cranially with the upper limb (Churchill, 1994;Bastir et al, 2013;Schmid et al, 2013).…”
Section: Introductionmentioning
confidence: 99%